Atypical Presentation of Disseminated Zoster in a Patient with Rheumatoid Arthritis - Nirav Patel; Davinder Singh; Krunal Patel; Shadab Ahmed; Prachi Anand (Case Reports in Medicine)
Patients with rheumatoid arthritis (RA) have 2-fold increased risk of herpes zoster. In literature, limited information exists about disseminated cutaneous zoster in RA patients. An 83-year-old African-American female with RA presented with generalized and widespread vesicular rash covering her entire body. Comorbidities include hypertension, type II diabetes, and dyslipidemia. Patient was on methotrexate 12.5 mg and was not receiving any corticosteroids, anti-TNF therapy, or other biological agents. The patient was afebrile (98 F) with no SIRS criteria. Multiple vesicular lesions were present covering patient’s entire body including face. Lesions were in different stages, some umbilicated with diameter of 2–7 cm. Many lesions have a rim of erythema with no discharge. On admission, patient was also pancytopenic with leukocyte count of 1.70 k/mm3. Biopsies of lesions were performed, which were positive for Varicella antigen. Subsequently, patient was started on Acyclovir. The patient’s clinical status improved and rash resolved. Our patient presented with “atypical” clinical picture of disseminated cutaneous zoster with no obvious dermatome involvement. Disseminated zoster is a potentially serious infection that can have an atypical presentation in patients with immunocompromised status. High index of suspicion is needed to make the diagnosis promptly and to initiate therapy to decrease mortality and morbidity.